Medically assisted gender affirmation: when children and parents disagree. Issue 5 (31st December 2019) - Dubin, Samuel; Lane, Megan; Morrison, Shane; Radix, Asa; Belkind, Uri; Vercler, Christian; Inwards-Breland, David
Abstract : Institutional guidelines for transgender children and adolescent minors fail to adequately address a critical juncture of care of this population: how to proceed if a minor and their parents have disagreements concerning their gender-affirming medical care. Through arguments based on ethical, paediatric, adolescent and transgender health research, we illustrate ethical dilemmas that may arise in treating transgender and gender diverse youth. We discuss three potential avenues for providing gender-affirming care over parental disagreement: legal carve-outs to parental consent, the mature minor doctrine and state intervention for neglect. Our discussion approaches this parent–child disagreement in a manner that prioritises the developing autonomy of transgender youth in the decision-making process surrounding medically assisted gender affirmation. We base our arguments in the literature surrounding the risks and benefits of gender-affirming therapy in transgender children and the existing legal basis for recognising minors' decision-making authority in certain medical situations.